Impact of Landfill on Surface Water Quality in Xay District, Oudomxay Province - PHANTHAVONG, Vongphone; CHANSOMPHOU, Vatthanamysay; VONGKHAMSY, Hoummala (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Maintaining a good surface water quality is a challenge for our environment. There are many factors that influence surface water quality and each of them needs to be thoroughly investigated. Amongst many, landfills are representing a major threat as a result of the increased waste generation, mainly due to urbanization and the continuous development. Wastewater and it is effluents are often discharged into surface water sources, which are receptacles for domestic and industrial wastes, resulting in the form of pollution. The poor quality of wastewater effluents is responsible for the degradation of the receiving surface water body. Wastewater effluent should be treated efficiently to avert adverse health risk of the user of surface water resources and the aquatic ecosystem. The release of raw and improperly treated wastewater into water courses has both short‐ and long‐term effects on the environment and human health. This study determined the characteristics of random wastes with the reduction method. For the surface water study was carried out twice in different climates. The results of the study show that the garbage that is collected and dumped at the landfill is not separated from the source. Therefore, it will affect the surface water quality in Xay District, Oudomxay Province.